A space to promote culture, identity and patrimony at the Faculty of Physical Culture - Eyler Guerra-Pérez; Maricela Millet-Duperey (Universidad de Guantánamo, 2015)
This investigation introduces a study about the relationship culture- identity- cultural patrimony in Guantánamo, needed for the formation of an adequate General and Integral Culture at the Faculty of Physical Culture in the students. Some links have been established besides, for the achievement of the paper´s purpose through the systematization of the work of personalities, institutions and cultural happenings that have contributed to the processes of formation and development of the cultural local identity in the different periods of its evolution, which allows an integral understanding of the Cuban history in general and the local history in particular involving the cultural formation of new generations.